Periungual pyogenic granuloma-like lesions following plaster cast immobilization: a case managed with symptomatic therapy - Baykal, Can; Kilic, Sila; Sezer, Suat (Wiley, 2018)
[Abstract Not Available]
Periunguale pyogene Granulom-ähnliche Läsionen nach Gipsruhigstellung: Heilung durch symptomatische Therapie
Keywords: Reflex Sympathetic Dystrophy; Onychomadesis